ANALYSIS OF PRIMARY SCHOOL SCIENCE TEACHERS' PERCEPTIONS IN NORTH LAMPUNG ON SCIENCE LITERACY BASED ON EIGHT SCIENCE LITERACY INDICATORS - Rohmani Rohmani; I Wayan Distrik; Herpratiwi Herpratiwi; Dina Maulina (EDUSAINS, 2022)
One of the main skills that are part of the basic skills of the 21st century is critical thinking skills which are part of science literacy. The teacher's ability to educate their students determines the success of learning science literacy. This study aims to identify the science literacy perceptions of elementary school science teachers in North Lampung as a reference for developing science literacy learning in College. The data collection method is carried out by distributing website-based online questionnaires. The research subjects were elementary school science teachers in North Lampung. Data analysis was performed using the Rasch model to determine the level of reliability of respondents and item items and to determine the distribution of respondents' answers. The results of this study show that the level of reliability of the respondents is very good, with a value of 0.92, and the reliability of the items is quite good, with a value of 0.79. Further analysis was carried out to see the perceptions of elementary school science teachers on science literacy. The results of the analysis revealed that the perceptions of elementary school science teachers regarding science literacy based on eight indicators obtained an average percentage of 54.6% and is in the middle category range. From the results of data analysis, the findings in this study are the lack of ethics in science among elementary school science teachers in North Lampung. How To Cite: Rohmani, Distrik, W., Herpratiwi, Maulita, D. (2022). Analysis of Primary School Science Teachers' Perceptions in North Lampung on Science Literacy Based on Eight Science Literacy Indicators. EDUSAINS, 14 (2) : 162-174.